Amyloid-Beta Influences Memory via Functional Connectivity During Memory Retrieval in Alzheimer's Disease - Li, Binyin; Zhang, Miao; Jang, Ikbeom; Ye, Guanyu; Zhou, Liche; He, Guiying; Lin, Xiaozhu; Meng, Hongping; Huang, Xinyun; Hai, Wangxi; Chen, Shengdi; Li, Biao; et al. (Frontiers in Aging Neuroscience, 2021)
Objective: Amnesia in Alzheimer's disease (AD) appears early and could be caused by encoding deficiency, consolidation dysfunction, and/or impairment in the retrieval of stored memory information. The relationship between AD pathology biomarker β-amyloid and memory dysfunction is unclear. Method: The memory task functional magnetic resonance imaging and amyloid positron emission tomography were simultaneously performed to investigate the relationship between memory performance, memory phase-related functional connectivity, and cortical β-amyloid deposition. We clustered functional networks during memory maintenance and compared network connectivity between groups in each memory phase. Mediation analysis was performed for investigating the mediator between β-amyloid and related cognitive performance. Results: AD was primarily characterized by decreased functional connectivity in a data-driven Network composed of a priori default mode network, limbic network, and frontoparietal network during the memory maintenance (0.205 vs 0.236, p = 0.040) and retrieval phase (0.159 vs 0.183, p = 0.017). Within the Network, AD had more regions with reduced connectivity during the retrieval than maintenance and encoding phase (Chi-Square p = 0.01 and < 0.001). Furthermore, the global cortical β-amyloid negatively correlated with network connectivity during the memory retrieval phase (R = -0.247, p = 0.032), and the relationship mediated the effect of cortical β-amyloid on memory performance (average causal mediation effect = -0.05, p = 0.035). Conclusion: We demonstrated that AD had decreased connectivity in specific networks during the memory retrieval phase. Impaired functional connectivity during memory retrieval mediated the adverse effect of β-amyloid on memory. These findings help to elucidate the involvement of cortical Aβ in the memory performance in the early stages of AD.